ANTICANCER, ANTIOXIDANT AND IMMUNO-MODULATORY EFFECTS OF ACACIA HONEY IN SOME CANCER CELL LINES (2014)
Cancer is one of the leading causes of death worldwide. Cancer curative properties of honey have been documented. However, there is dearth of information on the exact mechanism of anticancer effect of honey. This study was designed to evaluate the antioxidant, immuno-modulatory and anticancer properties of "Acacia Honey" (AH). The AH used was obtained from Achida, Sokoto State, Nigeria and authenticated by pollen grain analysis. Antioxidant and immuno-modulatory properties of 0.125-2.5 % (v/v) AH and its dichloromethane, ethylacetate and aqueous fractions were investigated in blood, neutrophils and macrophages by luminol and lucigenin-amplified chemiluminescence methods. The AH cytotoxic and anti-proliferative effects on lymphocytes were evaluated by cytochalasin B- blocked micronucleus and mitotic index assays, respectively. Anti-proliferative effects of 0.5-10 % (v/v) AH on NIH/3T3, PC-3 and NCI-H460 cells were conducted using MTT (3-[4, 5-dimethyl Thiazole-2-yl]-2, 5-diphenyl-tetrazolium bromide), mitotic index and fluorescence-activated cell sorting methods. Cell cycle analysis and expressions of TNF-?, IL-1? and Prostate Specific Antigen (PSA) were done by flow cytometry and ELISA. Expressions of p53 and bcl-2 genes were done using real-time PCR. Male Wistar rats (112-200g) were randomly assigned to four groups of five (5) animals treated orally with distilled water (control), AH 20 % (v/v), Sodium Arsenite (SA) (5 mg/kg body weight), AH and SA daily for one week. The frequency of micronucleated polychromatic erythrocytes (mPCEs) was determined by microscopy. Levels of serum and tissue (brain and liver) lipid peroxidation (LPO), reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) were determined by spectrophotometry. Data were analyzed by one-way ANOVA and LSD at p = 0.05. In blood, neutrophils and macrophages, fractions of AH caused pro-oxidant effect while the unfractionated sample elicited antioxidant effect with IC50 of < 0.25, 0.20 and < 0.125 % respectively. The cytotoxicity index for control was 0.00 ± 0.00. In 0.5 %, 1.0 %, 2.0 % and 4 % (v/v) AH treated, cytotoxicity index were 5.66 ± 0.02, 4.50 ± 0.01, -1.22 ± 0.00 and - 4.79 ± 0.03 respectively. The mitotic, nuclear division and cytokinesis-block proliferation indices for the controls were 7.35 ± 0.64, 1.40 ± 0.02 and 1.38±0.01 respectively. These indices increased proportionately with increase in AH concentration. The AH exhibits cytotoxic effects on NIH/3T3, PC-3 and NCI-H460 cells with IC50 of 3.7, 1.9 and 7.5 % (v/v) respectively. Treatment with 2.0 %, 4.0 % and 8 % (v/v) AH significantly decreased PSA levels (430.0 ± 10.0, 425.1 ± 15.0, 420.1 ± 20.0 pg/mL respectively) relative to control (530.0 ± 0.01 pg/mL) in PC-3 cells. The AH (2.0 %, 4.0 % and at 8.0 % (v/v)) significantly and dose-dependently arrested G0/G1 in NCI-H460 and PC-3 cells. The AH significantly decreased TNF-?, p53, bcl-2 expressions while IL-1? was elevated in the cells. The SA significantly increased LPO (serum, brain and liver) and mPCEs levels while co-treatment with AH significantly decreased these levels with increased GSH, CAT and SOD. Acacia honey shows anticancer property by eliciting cytotoxic and antiproliferative effects on cancer cells via activation of apoptotic pathways and antioxidant activity.